Khilafah in the Context of the State of Pancasila (Law Research Review Quarterly, 2016)
Indonesia with a diversity of religions, ethnicities and cultures is a characteristic of national life. The slogan "Unity in Diversity" is able to show the attitude of unity. The choice of Pancasila as the nation's ideology has been tested for some time. Reform is a sign of dissatisfaction with the implementation of Pancasila. But reform is not merely free freedom. Reform must be interpreted as a reminder that the Pancasila agreement as the basis of a single binary state Ika must continue to be developed and strengthened. Pancasila, is the formulation and guideline of national and state life for all Indonesian people. Pancasila as the ideology of the nation is the result of exploring the values ​​that live in society, must be conveyed and taught to the community. It must be convinced that this country was founded by the founders of the nation to be united, sovereign, just and prosperous. The goal of the Indonesian nation must still be its realization. It does not necessarily conclude that the reformation of the Indonesian people, showing the State of Indonesia with Pancasila has failed and must change the ideology of the nation. The Khilafah as an invitation to form a state based on religion for the Pancasila state seems to be less relevant. This can be viewed from the historical, normative and philosophical side of the Indonesian nation.